Toward transplantation tolerance with adipose tissue-derived therapeutics - Cheng, Hui-Yun; Anggelia, Madonna Rica; Lin, Cheng-Hung; Wei, Fu-Chan (Frontiers in Immunology, 2023)
Solid organ and composite tissue allotransplanation have been widely applied to treat end-stage organ failure and massive tissue defects, respectively. Currently there are a lot of research endeavors focusing on induction of transplantation tolerance, to relieve the burden derived from long-term immunosuppressant uptake. The mesenchymal stromal cells (MSCs) have been demonstrated with potent immunomodulatory capacities and applied as promising cellular therapeutics to promote allograft survival and induce tolerance. As a rich source of adult MSCs, adipose tissue provides additional advantages of easy accessibility and good safety profile. In recent years, the stromal vascular fraction (SVF) isolated from adipose tissues following enzymatic or mechanical processing without in vitro culture and expansion has demonstrated immunomodulatory and proangiogenic properties. Furthermore, the secretome of AD-MSCs has been utilized in transplantation field as a potential “cell-free” therapeutics. This article reviews recent studies that employ these adipose-derived therapeutics, including AD-MSCs, SVFs, and secretome, in various aspects of organ and tissue allotransplantation. Most reports validate their efficacies in prolonging allograft survival. Specifically, the SVF and secretome have performed well for graft preservation and pretreatment, potentially through their proangiogenic and antioxidative capacities. In contrast, AD-MSCs were suitable for peri-transplantation immunosuppression. The proper combination of AD-MSCs, lymphodepletion and conventional immunosuppressants could consistently induce donor-specific tolerance to vascularized composite allotransplants (VCA). For each type of transplantation, optimizing the choice of therapeutics, timing, dose, and frequency of administration may be required. Future progress in the application of adipose-derived therapeutics to induce transplantation tolerance will be further benefited by continued research into their mechanisms of action and the development of standardized protocols for isolation methodologies, cell culture, and efficacy evaluation.